Oracle SQL - Hotka, Dan; Safari eBooks ([Place of publication not identified] : Prentice Hall, 2015)
"In this LiveLessons course, Oracle ACE Director Dan Hotka will teach you how to use the SQL query language, interpret business questions into SQL code, and how to use Where clauses sub-queries, complex table join conditions, and how to create table objects and populate tables with data. Students will also learn how to access Oracle from Microsoft products such as Excel. In addition, they will learn how analytical SQL can be used for business analysis. This course will use both Toad and SQL Developer for SQL examples."--Resource description page.
Title taken from title screen (Safari, viewed July 7, 2015).
Presenter, Dan Hotka.
Keywords: Oracle (Computer file); SQL (Computer program language); Electronic books